Tristetraprolin inhibits macrophage IL-27-induced activation of antitumour cytotoxic T cell responses. Issue 1 (December 2017) - Wang, Qinghong; Ning, Huan; Peng, Hui; Wei, Lin; Hou, Rong; Hoft, Daniel; Liu, Jianguo
Abstract IFN-γ-producing cytotoxic T lymphocytes are essential for host defense against viral infection and cancer. Here we show that the RNA-binding tristetraprolin, encoded byZfp36, is needed for CD8+ T-cell production of IFN-γ in vivo. When activated in vitro, however, IFN-γ production by naive wild type and tristetraprolin-deficient CD8+ T-cells is comparable. IL-27 is overproduced by tristetraprolin-deficient macrophages and increased systemically in tristetraprolin-deficient mice. Tristetraprolin suppresses IL-27 production by promoting p28 mRNA degradation. Importantly, deletion of IL-27 receptor WSX-1 in tristetraprolin-deficient mice (WSX-1/tristetraprolin double knockout) leads to a reduction in cytotoxic T lymphocyte numbers. Moreover, tumor growth is accelerated, not only in tristetraprolin-deficient mice after cytotoxic T lymphocyte depletion, but also in WSX-1/tristetraprolin double knockout mice, with substantial reduction in the number of tumor cytotoxic T lymphocytes. This study describes a regulatory pathway for IL-27 expression and cytotoxic T lymphocyte function mediated by tristetraprolin, contributing to regulation of antitumour immunity. IL-27 is one of a number of cytokines that can induce antitumour CD8+ T cell responses. Here the authors show that TTP, encoded byZfp36, degrades p28 to inhibit IL-27 production by macrophages and is thereby a negative regulator of the antitumour response.